Відношення логічного наслідку в логіках квазіарних предикатів - Шкільняк, О.С. (Проблеми програмування, 2016)
Вивчаються відношення логічного наслідку в логіках тотальних однозначних, часткових однозначних, тотальних неоднозначних та часткових неоднозначних предикатів. Поряд із розглянутими раніше відношеннями типів T, F, TF, IR, DI, для логік квазіарних предикатів запропоновано і досліджено відношення типів T∨F та С. Описано властивості відношень логічного наслідку. Наведено приклади, які засвідчують відмінності розглянутих відношень. Показана нетранзитивність відношень типів T∨F та С, можливість моделювання відношень типу С за допомогою відношень типу TF. Встановлено співвідношення між різними відношеннями логічного наслідку. Изучаются отношения логического следствия в логиках тотальных однозначных, частичных однозначных, тотальных неоднозначных и частичных неоднозначны предикатов. Наряду из ранее рассмотренными отношениями типов T, F, TF, IR, DI, для логик квазиарных предикатов предлжены и исследованы отношения типов T∨F и С. Описаны свойства отношений логического следствия. Приведены примеры, свидетельствующие о различии рассмотренных отношений. Показана нетранзитивность отношений типов TvF и С, возможность моделирования отношений типа С с помощью отношений типа TF. Установлены соотношения между различными отношениями логического следствия. Logical consequence is one of the most fundamental concepts in logic. A wide use of partial (sometimes many-valued as well) mappings in programming makes important the investigation of logics of partial and many-valued predicates and logical consequence relations for them. Such relations are a semantic base for a corresponding sequent calculi construction. In this paper we consider logical consequence relations for composition nominative logics of total single-valued, partial single-valued, total many-valued and partial many-valued quasiary predicates. Properties of the relations can be different for different classes of predicates; they coincide in the case of classical logic. Relations of the types T, F, TF, IR and DI were investigated in the earlier works. Here we propose relations of the types T∨F and С for logics of quasiary predicates. The difference between these two relations manifests already on the propositional level. Properties of logical consequence relations are specified for formulas and sets of formulas. We consider partial cases when one of the sets of formulas is empty. It is shown that relations P|=T∨F and R|=С are non-transitive, some properties of decomposition of formulas are not true for R|=С, but at the same time the latter can be modelled through R|=TF. A number of examples demonstrates particularities and distinctions of the defined relations. We also establish a relationship among various logical consequence relations.